Metastatic prostate cancer‐associated P62 inhibits autophagy flux and promotes epithelial to mesenchymal transition by sustaining the level of HDAC6. Issue 6 (31st January 2018) - Jiang, Xianhan; Huang, Yiqiao; Liang, Xue; Jiang, Funeng; He, Yongzhong; Li, Tian; Xu, Guibin; Zhao, Haibo; Yang, Weiqing; Jiang, Ganggang; Su, Zhengming; Jiang, Lingke; et al.
Abstract : Background: P62 (also named sequestosome‐1, SQSTM1) is involved in autophagy regulation through multiple pathways. It interacts with autophagosomes‐associated LC3‐II and ubiquitinated protein aggregates to engulf the aggregates in autophagosomes, interacts with HDAC6 to inhibit its deacetylase activity to maintain the levels of acetylated α‐tubulin and stabilities of microtubules to enhance autophagosome trafficking, and regulates autophagy initiation and cell survival. We performed immunohistochemistry staining of P62 in prostate tissues from prostate cancer patients and found that levels of P62 in patients with prostate adenocarcinomas (PCA) are significantly higher than those in patients with benign prostate hyperplasia (BPH). High levels of P62 predict high tumor grade and high intensity of metastasis. Methods: We created prostate cancer cell lines stably overexpressing P62 and then suppress the expression of P62 in the cell line stably overexpressing P62 with CRISPR technology. Cell proliferation assay with crystal violet, cell migration assay, cell invasion assay, Western blot analysis, and confocal fluorescent microscopy were conducted to test the impact of altered levels of P62 on the growth, migration, invasion, epithelial‐to‐mesenchymal transition, autophagy flux, HDAC6 activity, and microtubular acetylation of cancer cells. Results: P62 increased the levels of HDAC6 and reduced the acetylation of α‐tubulin and the stability of microtubules. Consequently, high levels of P62 caused a promotion of epithelial‐to‐mesenchymal transition in addition to an impairment of autophagy flux, and further led to an enhancement of proliferation, migration, and invasion of prostate cancer cells. Conclusion: P62 promotes metastasis of PCA by sustaining the level of HDAC6 to inhibit autophagy and promote epithelial‐to‐mesenchymal transition.